Esophageal perforations secondary to endoscopic procededures (report of three cases) - Ahmet TEZEL; Tülin ŞAHİN and Yasemin KOŞAR and Dilek OĞUZ and Kemal ARDA and Burhan ŞAHİN and Turhan CUMHUR (Turkish Journal of Gastroenterology, 2019)
-